Pendampingan Ibu Rumah Tangga dalam Upaya Memutus Mata Rantai Covid-19 di Desa Klagensrampat-Lamongan - Hasyim; Annisa Nidaur Rohmah; Siti Mahmudah (TAAWUN, 2021)
Efforts to Break the Covid-19 Chain through Strengthening the Role of Housewives in Klagensrampat Village, Maduran Lamongan in 2020 aims to increase understanding and build cooperation with the community in handling Covid-19 prevention. The method in implementing this program assistance is in the form of delivering knowledge transformation in providing understanding about the socialization of Covid-19 in terms of health, socialization in terms of religion, and socialization in terms of social and culture. The result of these efforts is the creation of education on preventing the transmission of Covid-19.